Laminarin ameliorates alcohol‐induced liver damage and its molecular mechanism in mice. Issue 12 (14th December 2022) - Guo, Tianyi; Zhu, Lingfeng; Zhou, Yaping; Han, Shuai; Cao, Yunyun; Hu, Zuomin; Luo, Yi; Bao, Liyuan; Wu, Xiuxiu; Qin, Dandan; Lin, Qinlu; Luo, Feijun
Abstract: Alcoholic liver disease (ALD) has become a health issue globally. Laminarin, a low molecular weight marine‐derived β‐glucan, has been identified with multiple biological activities. In this study, the ameliorative effect on ALD of laminarin isolated from brown algae was investigated. Phenotypic, pathological alterations and biochemical characteristics indicated that laminarin administration (100 mg/kg/day) significantly alleviated liver injury and improved liver function in the alcohol‐induced mice. Gene chip results indicated that laminarin treatment caused 52 up‐regulated and 13 down‐regulated genes in the hepatic tissues of alcohol‐induced damage mice, and most of these genes are associated with regulation of oxidative stress (such as CYP450/glutathione‐dependent antioxidation), Wnt signaling pathway, retinol metabolism, and cAMP pathway based on GO and KEGG analysis. PPI network analysis indicated that the downstream target genes lied in the hub of the net. Our experiments also confirmed the changed expressions of some target genes. Taken together, these results suggest that laminarin can ameliorate alcohol‐induced damage in mice and its molecular mechanism lies in modulating anti‐oxidation pathway, WNT pathway, and cAMP pathway, which regulate the expressions of downstream target genes and alleviate alcohol‐induced damage. Our study provides new clue to prevent alcohol‐induced damage and will be benefit to develop functional foods. Practical applications: This study verified the positive effect on alcoholic liver disease (ALD) of laminarin, a water‐soluble brown algae‐derived β‐glucan, linked by β‐(1, 3) glycosidic bonds with β‐(1, 6) branches. Laminarin significantly alleviated liver injury and improved liver function of ALD mice. Moreover, transcriptomics and bioinformatics analysis further revealed the gene expression patterns, hub targets, and signalings including CYP450/glutathione, Wnt, retinol metabolism, cAMP pathways regulated by laminarin. This research is the first evidence for hepatoprotective effect of laminarin against ALD and its molecular mechanism, which will be advantage to develop functional foods or adjuvant therapy of ALD. Abstract : The marine‐derived β‐glucan laminarin alleviates liver damage of ALD mice; Laminarin regulates hepatic ALD‐related gene expressions; Laminarin ameliorates ALD through regulation of CYP450, retinol metabolism, Wnt, and cAMP pathway.